2010
DOI: 10.1016/j.neuropharm.2010.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of inhibition of CaV3.1 T-type calcium current by aliphatic alcohols

Abstract: Many aliphatic alcohols modulate activity of various ion channels involved in sensory processing and also exhibit anesthetic capacity in vivo. Although the interaction of one such compound, 1-octanol (octanol) with different T-type calcium channels (T-channels) has been described, the mechanisms of current modulation and its functional significance are not well studied. Using patch-clamp technique, we investigated the mechanisms of inhibition of T-currents by a series of aliphatic alcohols in recombinant human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…Surprisingly, we found that IFL did not affect resting membrane potential and input resistance. These findings are in line with the previously reported inhibitory effect of another anesthetic, aliphatic alcohol octanol, on T-current, along with unchanged passive membrane properties in TC neurons (Eckle and Todorovic 2010). A possible explanation of these divergent findings between our and Puil’s group is not immediately obvious, but some possibilities include: internal biological variability within the rat phenotypes; different environmental, nutritional, and housing conditions; and a possible difference in the recording conditions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Surprisingly, we found that IFL did not affect resting membrane potential and input resistance. These findings are in line with the previously reported inhibitory effect of another anesthetic, aliphatic alcohol octanol, on T-current, along with unchanged passive membrane properties in TC neurons (Eckle and Todorovic 2010). A possible explanation of these divergent findings between our and Puil’s group is not immediately obvious, but some possibilities include: internal biological variability within the rat phenotypes; different environmental, nutritional, and housing conditions; and a possible difference in the recording conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Transitions from closed to inactivated states can be measured using long conditioning prepulses at varying potentials, producing what are commonly referred to as steady-state inactivation curves. We assessed steady-state inactivation curves using our standard double-pulse protocol with 3.5-s long prepulses to variable voltages (from −110 to −50 mV in 5-mV increments) and V t to −50 mV (Eckle and Todorovic 2010). The two panels of Figure 3A show representative traces of the currents in the same TC cell before the application of IFL (control, left) and after 10 min of application of 2 vol% of IFL (right).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca V 3.1 channels are largely inactive at resting potential and recover from inactivation in both a time-and voltage-dependent manner. Both 10 and 100 mM ethanol accelerated the recovery from inactivation, similar to the effect of long-chain alcohols (20). Because the voltage-dependence of inactivation was not affected and the deinactivation kinetics were not slowed, the decrease in I T must have been due to a decrease in conductance and/or number of available channels.…”
Section: Resultsmentioning
confidence: 61%
“…In addition, hyperpolarization-activated cyclic nucleotide-gated (HCN) channels that conduct I h also facilitate rebound firing in IO neurons (18). In rodents, I T was inhibited acutely by ethanol and long-chain aliphatic alcohols (19,20), whereas I h was augmented by ethanol (21). Recent studies demonstrated that the tremor mediated by the IO requires Ca V 3.1 T-type calcium channels (22,23) and is synchronized by gap junctions (24).…”
mentioning
confidence: 99%